Genetic Divergence in Groundnut (Arachis hypogaea L) - Zaman, MA; Tuhina-Khatun, M; Moniruzzaman, M; Yousuf, MN (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Comprising 34 groundnut genotypes an experiment was conducted in a randomized block design with three replication at the Research farm of Regional Agricultural Research Station, BARI, Hathazari, Chittagong during Rabi season (December 2009 to April 2010) for estimation of the multivariate analysis of divergence. The genotypes were grouped into five clusters. Cluster III contained the highest number of genotypes (12) and the cluster II contained the lowest (2). The inter-cluster distances in all cases were larger than the intra-cluster distance which indicated that wider diversity is present among the genotypes of distant grouped. The highest intra cluster distance was observed in cluster V and the lowest in II. The highest inter cluster distance was observed between the cluster IV and III followed by V and III and the lowest between cluster V and I. Days to 50% flowering, days to maturity, number of branches per plant, number of matured nuts per plant and karnel size were the most important contributors based on the latent vector. But the highest cluster means for matured nuts per plant, 100 karnel weight, 100 nuts weight and yield per plant were obtained from the cluster II. With moderate yield but early maturity varieties were found in cluster IV. Therefore, more emphasis should be given on cluster VI for selecting genotypes as parents for crossing with the genotypes of cluster II and III for getting new recombinants with early maturity and higher yield. Key Words: Genetic divergence; cluster analysis; D2 analysis; groundnut (Arachis hypogaea L) DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9317 BJPBG 2010; 23(1): 45-49